Analysis of Compensation, Motivation, Level of Stress on Work Performance in PT. Mitra Agung Mustika - Bobby Surya Darma; Dewi Nurmasari Pane; Ocdy Amelia (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
This study uses a quantitative model that is the population here the researcher uses all employees that occur in PT. Mitra Agung Mustika numbered 31 respondents and here the business owner or owner is not included in my respondents so the sample I use is saturated sample, meaning all that is the population appointed as a sample. sampling is all employees in the company PT. Mitra Agung Mustika. The data used is primary data, and based on the distribution of questionnaires and distribution of questionnaires to respondents or all employees. The result of F test yielded Fhitung22.572> Ftabel 2.97 so that Ha is accepted and Ho is rejected, meaning compensation, Motivation, Stress level affect Job Performance. Until the previous hypothesis (Ha) is accepted. And the result of the calculation for the variables of compensation, motivation and stress level with SPSS obtained a result of 68.3% and the remaining 31.7% of the overall effect of variable X on Y.